(untitled) - Heinrichs, E. A. (Cambridge, UK, 2017)
The rice plant is an ideal host for many insect species. All of the plant parts are vulnerable to insect-feeding from the time of sowing till harvest. There are over 800 insect species damaging rice in one way or another, although the majority of them do very little damage. In tropical Asia only about 20 species are of major importance. In Africa, 15 species of insects are considered major rice pests and in the Americas about 20 species are considered major pests.
Keywords: Rice,Insect pests; Diseases and pests